It's the end of the world but it's a beautiful day [compact disc] (Concord Records, 2023)
Multi-platinum-selling artist Thirty Seconds To Mars makes a triumphant return with their sixth studio album. The record heralds a new era for the band, one that not only explores the darker sides of the human experience but the hope as well, an arresting reminder that even in the face of seemingly impossible obstacles, there is still beauty to be found in the world.